THE IMPACT OF FREE PRIMARY EDUCATION ON QUALITY OF PRIMARY EDUCATION IN NAKURU EAST SUB COUNTY, NAKURU COUNTY, KENYA - Lydiah, Gachie Wanjiku; J. Kathuri, Prof. Nephat; Mungai, Ms. Sarah (IJRDO- Journal of Educational Research, 2017)
The purpose of this study was to investigate the impact of the Free Primary Education on quality of primary education in Nakuru East Sub- County of Nakuru County, Kenya. The specific objectives of the study were to investigate the impact of Free Primary Education on teaching and learning facilities, to identify the effect of funds for Free Primary Education on the quality of education and to determine the influence of pupils’ enrolment on the academic achievement of pupils under the Free Primary Education programme. It was concluded that teaching and learning facilities negatively affected the implementation of FPE leading to poor quality of education due to the inadequacy of the teaching and learning materials. The level of funding affected the quality of education either because it was delayed or unavailable